Slow-growing large pleomorphic adenoma of ectopic lacrimal gland tissue in the upper eyelid - Alsuhaibani, Adel H. (Elsevier, 2012)
A few cases of pleomorphic adenoma of an ectopic lacrimal gland involving the deep orbit and lateral canthus have been previously reported. A 75-year-old female with a slow-growing, large pleomorphic adenoma arising from ectopic lacrimal gland tissue in the left upper eyelid is described in the present case report.